MINDMITRA (International Journal of Scientific Research in Science and Technology, 2026)
The Bhagavad Gita is a timeless source of spiritual and philosophical knowledge that provides guidance on human behavior, ethical decision-making, and self-realization. In today’s fast-paced digital world, individuals often face challenges such as stress, lack of focus, confusion, and imbalance between personal and professional life. Although the teachings of the Bhagavad Gita offer practical solutions to these issues, they are not widely accessible in a structured, interactive, and user-friendly format suitable for modern learners. This research paper presents the design and development of a Bhagavad Gita- based Learning Management System (LMS), which aims to integrate ancient wisdom with modern digital technology. The proposed system provides a structured platform where users can register, log in, and access personalized learning content based on their interests, preferences, and level of understanding. Key features of the system include secure user authentication, profile management, and personalized onboarding, which help in delivering a customized learning experience to each user. The system emphasizes both theoretical understanding and practical application of the Gita’s teachings. By offering tailored learning paths, the platform enhances user engagement and helps individuals apply spiritual principles in their daily lives. This contributes to improved mental clarity, emotional stability, ethical thinking, and better decision-making abilities. In conclusion, the proposed LMS serves as a bridge between ancient spiritual knowledge and modern technological advancements. It provides an innovative, accessible, and effective approach to learning the teachings of the Bhagavad Gita, thereby promoting overall well-being and holistic personal development.